2022
DOI: 10.1097/icu.0000000000000934
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in glaucoma: posterior segment optical coherence tomography

Abstract: Purpose of reviewTo summarize the recent literature on deep learning (DL) model applications in glaucoma detection and surveillance using posterior segment optical coherence tomography (OCT) imaging. Recent findingsDL models use OCT derived parameters including retinal nerve fiber layer (RNFL) scans, macular scans, and optic nerve head (ONH) scans, as well as a combination of these parameters, to achieve high diagnostic accuracy in detecting glaucomatous optic neuropathy (GON). Although RNFL segmentation is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Most studies on glaucoma detection have relied on color fundus photography (CFP) due to its accessibility and low cost [2 ▪ ,3–6]. Optical Coherence Tomography (OCT)-based DL models using conventional 2D B scans, 3D volumetric scans or OCT-angiography have yielded excellent accuracy [3–5,7 ▪ ]. Visual Field (VF)-based glaucoma detection models also showed good accuracy but are associated with inherent challenges like noisy data, cost and time-consumption [2 ▪ ,3].…”
Section: Detecting Glaucoma With Artificial Intelligence In Different...mentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies on glaucoma detection have relied on color fundus photography (CFP) due to its accessibility and low cost [2 ▪ ,3–6]. Optical Coherence Tomography (OCT)-based DL models using conventional 2D B scans, 3D volumetric scans or OCT-angiography have yielded excellent accuracy [3–5,7 ▪ ]. Visual Field (VF)-based glaucoma detection models also showed good accuracy but are associated with inherent challenges like noisy data, cost and time-consumption [2 ▪ ,3].…”
Section: Detecting Glaucoma With Artificial Intelligence In Different...mentioning
confidence: 99%
“…The ability of OCT data to be used in DL models to detect glaucoma has been well established [7 ▪ ]. It has been recently suggested that unsegmented retinal nerve fiber layer (RNFL) B-scans or three-dimensional optic disc volumetric/cube scans may be more promising for AI-mediated glaucoma (progression) detection than scans with automated segmentation [2 ▪ ,5,7 ▪ ]. Recent studies employed different methodologies to improve model accuracy and explore newer regions of interest in OCT scans.…”
Section: Detecting Glaucoma With Artificial Intelligence In Different...mentioning
confidence: 99%
See 2 more Smart Citations
“…There is a lot of interest in using artificial intelligence (AI) to help diagnose diseases at an earlier stage, identify biomarkers that may not be readily apparent to the clinician, and to follow disease progression over time. Chen et al [1] discuss using AI models with optical coherence tomography to diagnose and follow eyes with glaucoma. This type of work has direct applicability to other conditions, including macular degeneration as well as corneal diseases.…”
mentioning
confidence: 99%